2014
DOI: 10.9788/tp2014.3-05
|View full text |Cite
|
Sign up to set email alerts
|

Matlab and eye-tracking: Applications in psychophysics and basic psychological processes

Abstract: This article aims to demonstrate the utilities of Matlab (MATrix LABoratory) and eye-tracker for research in psychophysics and basic processes. We fi rst introduce its origin, functioning, and advantages over other programs, and then we review different applications of Matlab in psychophysical tests involving eye-trackers. As an example, we present the development of a psychophysical test involving eye-tracker and Matlab, showing its ability to communicate and interact with other devices and programming langua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 20 publications
1
15
0
1
Order By: Relevance
“…In the literature on this theme, for instance, no studies on eye tracking that use a visual task similar to the visual maze used in this study are found. Considering the results obtained, the Visual Maze Test demonstrates that it is an efficient task for evaluating visual information processing, resistant regarding psychosocial and individual factors, and is in line with a previous study in which this test is described [40]. However, additional studies that use this test are needed.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…In the literature on this theme, for instance, no studies on eye tracking that use a visual task similar to the visual maze used in this study are found. Considering the results obtained, the Visual Maze Test demonstrates that it is an efficient task for evaluating visual information processing, resistant regarding psychosocial and individual factors, and is in line with a previous study in which this test is described [40]. However, additional studies that use this test are needed.…”
Section: Discussionsupporting
confidence: 82%
“…Eye movements were recorded through a binocular, 300 Hz, Tobii eye tracker, attached to a 23” monitor (1920 x 1080 pixel maximum resolution and 300 cd/m 2 max luminance) on which the Visual Maze Test (70,42 cd/m 2 luminance) [40] was presented for the participants to visualize. The system, integrated into a Dell Latitude 3450 notebook with a 14" HD monitor (1366 x 768) and Windows 8.1 Pro 64 bit operational system, Intel Core i7-5500U 2.4 GHz processor, and 8 GB RAM memory, was used to monitor the test.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Através das avaliações psicofísicas, pesquisadores desenvolveram testes de avaliação da percepção visual através de imagens acromáticas e acromáticas. Todavia, técnicas eletrofisiológicas e de rastreamento do movimento ocular são baseadas em novas tecnologias que também permitem uma descrição apurada da apresentação do estímulo, registro, sincronização e análise (Santos et al, 2014).…”
Section: Avaliação Do Rastreamento Do Movimento Ocularunclassified